OVARIAN LEYDIG CELL TUMOR: A MYSTERIOUS CAUSE OF SEVERE VIRILIZATION - Gitsomboon, Sawika; Kampiwtha, Suthinee; Poorichitiporn, Arnon; Wasinghon, Pornsawan; Chunlakitchawat, Yingyot (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 41-year-old woman with uterine bleeding and progressive virilization for 5 years was referred to our hospital because of worsening anemia. Abdominal CT and transvaginal ultrasound showed an enlarged uterus and left ovary without any tumor. She underwent abdominal hysterectomy and was diagnosed with leiomyoma then evaluated for virilization. Laboratory findings were a total testosterone level of 644 ng/dl (reference, 14-53 ng/dl), DHEAS and 17-OHP levels were normal. 8 am cortisol level after 1 mg dexamethasone suppression test was suppressible. According to markedly high testosterone levels and normal adrenal androgen levels, an androgensecreting ovarian tumor was highly suggestive. Since the patient suffered from severe virilization and did not desire fertility, she underwent bilateral oophorectomy. The histopathology result showed a Leydig cell tumor on the left ovary. At the follow-up clinic, where she is receiving estrogen replacement, her testosterone level returned to a normal level and virilization was gradually improved.